Faked Mastery, or Who Inspired Tarkovsky’s Boriska? - Duoblienė, Lilija (Religija ir kultūra, 2016)
[full article and abstract in Lithuanian; abstract in English]This article discusses the concept of mastery and the master in the Middle Ages and how it is treated in the present artistic context. The historical approach and the various sources that reconstruct this concept are put into an artistic context that is partly based on medieval tradition and partly interprets it. We choose for that Andrei Tarkovsky’s film Andrei Rublev and its Bell episode, in which young Boriska pretends to be a master and is looking for a way to prove this mastery of his. This film allows to interpret medieval tradition of crafts and training newly breaking the established order, also establishing some connections with Gilles Deleuze’s concept of creativity and the special role of the craftsman. Deleuze’s attention to Tarkovsky’s work, especially the film Andrei Rubliov, provides plenty of insights and unexpected meanings in the context of such a comparison.
Keywords: Tarkovsky; Deleuze; concept of mastery; relationship with reality